PEMBELAJARAN KHULASAH NURUL YAQIN DI DAYAH DARUSSA’DAH COT TAROM BAROH (Pascasarjana Institut Agama Islam Almuslim Aceh, 2024)
The factual issue at Dayah Darussa'adah Cot Tarom Baroh is that there are still many students who do not fully understand the learning of Khulasah Nurul Yaqin, therefore researchers are interested in examining what methods are used by teachers in learning Khulasah Nurul Yaqin at Dayah Darussa'adah Cot Tarom Baroh . The research that the author used in this research is a qualitative method. Primary data is produced as a result of interactions between researchers and sources who know the learning process of Khulasah Nurul Yaqin at Dayah Darussa'adah Cot Tarom Baroh, and secondary data is information obtained from second parties, in the form of people, books or notes of a documentary nature. The research results obtained are the methods used in learning the book Khulasah Nurul Yaqin at Dayah Darussa'adah Cot Tarom Baroh Bireuen, namely using the lecture method, mutala'ah method and question and answer method